Remote ischemic preconditioning ameliorates indirect acute lung injury by modulating phosphorylation of IκBα in mice. Issue 2 (February 2019) - Kim, Yun-Hee; Kim, Young-Sung; Kim, Byung-Hwa; Lee, Kuen-Su; Park, Hyung-Sun; Lim, Choon-Hak
Objective: Acute lung injury is responsible for mortality in seriously ill patients. Previous studies have shown that systemic inflammation is attenuated by remote ischemic preconditioning (RIPC) via reducing nuclear factor-kappa B (NF-κB). Therefore, we investigated whether lipopolysaccharide (LPS)-induced indirect acute lung injury (ALI) can be protected by RIPC. Methods: RIPC was accomplished by 10 minutes of occlusion using a tourniquet on the right hind limb of mice, followed by 10 minutes of reperfusion. This process was repeated three times. Intraperitoneal LPS (20 mg/kg) was administered to induce indirect ALI. Inflammatory cytokines in bronchoalveolar lavage fluid were analyzed using an enzyme-linked immunosorbent assay. Pulmonary tissue was excised for histological examination, and for examining NF-κB activity and phosphorylation of inhibitor of κBα (IκBα). Results: NF-κB activation and LPS-induced histopathological changes in the lungs were significantly alleviated in the RIPC group. RIPC reduced phosphorylation of IκBα in lung tissue of ALI mice. Conclusions: RIPC attenuates endotoxin-induced indirect ALI. This attenuation might occur through modification of NF-κB mediation of cytokines by modulating phosphorylation of IκBα.